PERAN PENYULUH DALAM PENGEMBANGAN KELOMPOK TANI DI DESA WAILAMUNG, KECAMATAN TALIBURA KABUPATEN SIKKA - Anggriani, Yohana; Evenandre Sato, Paulino (Universitas Cokroaminoto Palopo, 2024)
The aim of this study is to find out the role of extension workers and the relationship between the roles of extension workers in the development of farmer groups. This study was carried out in Wailamung Village, Talibura District, Sikka Regency from 20 July to 20 August 2024. The research method was carried out deliberately (Purposive Sampling) with the consideration that the location was a plantation crop center area. The results of the study show that the role of agricultural instructors in developing farmer groups is in accordance with the average score of the overall indicators given by respondents, namely motivator 2.83, facilitator 2.53, and educator 2.68, including in the high category or can be categorized as having played a role in carrying out their duties as motivator, facilitator and educator. . There is a significant relationship between the role of agricultural instructors in developing farmer groups in Wailamung Village, Talibura District, Sikka Regency: The role of agricultural instructors in developing farmer groups as Facilitators, Motivators and Educators.